Beyond the acute phase: a comprehensive literature review of long-term sequelae resulting from infectious diseases - Izquierdo-Condoy, Juan S.; Vásconez-Gonzáles, Jorge; Morales-Lapo, Estefanía; Tello-De-la-Torre, Andrea; Naranjo-Lara, Patricio; Fernández, Ricardo; Hidalgo, Marlon R.; Escobar, Adriana; Yépez, Vanessa Herrera; Díaz, Ana María; Oliva, Carlos; Ortiz-Prado, Esteban (Frontiers in Cellular and Infection Microbiology, 2024)
Infectious diseases have consistently served as pivotal influences on numerous civilizations, inducing morbidity, mortality, and consequently redirecting the course of history. Their impact extends far beyond the acute phase, characterized by the majority of symptom presentations, to a multitude of adverse events and sequelae that follow viral, parasitic, fungal, or bacterial infections. In this context, myriad sequelae related to various infectious diseases have been identified, spanning short to long-term durations. Although these sequelae are known to affect thousands of individuals individually, a comprehensive evaluation of all potential long-term effects of infectious diseases has yet to be undertaken. We present a comprehensive literature review delineating the primary sequelae attributable to major infectious diseases, categorized by systems, symptoms, and duration. This compilation serves as a crucial resource, illuminating the long-term ramifications of infectious diseases for healthcare professionals worldwide. Moreover, this review highlights the substantial burden that these sequelae impose on global health and economies, a facet often overshadowed by the predominant focus on the acute phase. Patients are frequently discharged following the resolution of the acute phase, with minimal long-term follow-up to comprehend and address potential sequelae. This emphasizes the pressing need for sustained vigilance, thorough patient monitoring, strategic health management, and rigorous research to understand and mitigate the lasting economic and health impacts of infectious diseases more fully.